Perbedaan Kelelahan Akibat Kerja Antara Shift Pagi, Siang Dan Malam Pada Karyawan Di Bagian Produksi Winding Pt. Bintang Makmur Sentosa Tekstil Industri, Sambung Macan, Sragen - Sari, Kiki Puspita; , Tarwaka, PGDip Sc, M.Erg; , Dwi Astuti, SKM, M.Kes (2016)
The work shift is one of factors which influences the occurence of exhaustion especially the day shift and the night shift. These two shifts are really more exhausted than the morning shift because they result in the disorder of circadian rhythm (sleeping disorder). The purpose of this research is to know the difference of exhaustion due to work among the morning shift, the day shift and the night shift in the employees of the winding production division. The method of this research used a cross sectional method. The statistic test used the test of kruskal wallis. The results of the research reveals that there are differences in the exhaustion due to work among the morning shift, the day shift and the night shift with the value of p=0.000 in the employees of the winding production division. Related to the level of work exhaustion in the employees, it is known that most of respondents are in the high exhaustion in the night work shift (35.5%).